The Perceived Value Of Online Games On Digital Customer Experience - Nathan Giharis; Popy Rufaidah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The expansion of the online gaming industry in Indonesia is correlated with its user base, which reached 174.1 million in 2022 and is projected to grow to 192.1 million in 2025. Technological advances, especially mobile gaming in Industry 4.0, have brought significant changes. Digital transformation has become important to attract new customers and improve their experience. Research on perceived value in digital customer experiences in online games is scarce, indicating a research gap. Previous research shows that perceived value influences user experience. This study examines how emotional, social, functional, and quality values influence digital customer experiences in online games. Statistical analysis validates the significant impact, Consistent with prior studies, the impact of these values affects the digital customer experience. Critical to strategic decision making emphasizes the importance of understanding customer perceptions and experiences.